What do we know about effectiveness of adaptation in reducing climate risks? A review of methodologies and evidence on adaptations in the agri-food systems - Koo, Jawoo; Reymondin, Louis; Ó Fionnagáin, Dúalta; O'Farrell, Jemima; Geever, Michael; Codyre, Patricia; Golden, Aaron; Spillane, Charles (2023)
In this session, speakers discuss methodologies and challenges for measuring effectiveness of adaptation and the various tools that can be deployed for the same by drawing upon examples from the agri-food sector. In doing so, the speakers will draw upon from the recently concluded IPCC WGII report, and from experiences of various scientific and implementing organizations including the CGIAR and look at a range of methodologies from impact evaluations, meta-reviews and satellite images (Reymondin, L.; Golden, A.; Spillan, C. (2022).